Toward Aerogel Electrodes of Superior Rate Performance in Supercapacitors through Engineered Hollow Nanoparticles of NiCo2O4. Issue 12 (8th November 2017) - Li, Jianjiang; Chen, Shuai; Zhu, Xiaoyi; She, Xilin; Liu, Tongchao; Zhang, Huawei; Komarneni, Sridhar; Yang, Dongjiang; Yao, Xiangdong
Abstract: A biomass‐templated pathway is developed for scalable synthesis of NiCo2 O4 @carbon aerogel electrodes for supercapacitors, where NiCo2 O4 hollow nanoparticles with an average outer diameter of 30–40 nm are conjoined by graphitic carbon forming a 3D aerogel structure. This kind of NiCo2 O4 aerogel structure shows large specific surface area (167.8 m 2 g −1 ), high specific capacitance (903.2 F g −1 at a current density of 1 A g −1 ), outstanding rate performance (96.2% capacity retention from 1 to 10 A g −1 ), and excellent cycling stability (nearly without capacitance loss after 3000 cycles at 10 A g −1 ). The unique structure of the 3D hollow aerogel synergistically contributes to the high performance. For instance, the 3D interconnected porous structure of the aerogel is beneficial for electrolyte ion diffusion and for shortening the electron transport pathways, and thus can improve the rate performance. The conductive carbon joint greatly enhances the specific capacity, and the hollow structure prohibits the volume changes during the charge–discharge process to significantly improve the cycling stability. This work represents a giant step toward the preparation of high‐performance commercial supercapacitors. Abstract : A hollow NiCo2 O4 @carbon aerogel is synthesized by a biomass‐template approach utilizing the ion‐exchange process between metal ion and sodium alginate solution. This type of NiCo2 O4 @carbon aerogel shows large specific surface area, high specific capacitance, outstanding rate performance, and excellent cycling stability for the supercapacitor.